EVALUATION OF THE LEVEL OF INDUSTRY CONCENTRATION IN REGIONS OF UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The article focuses on the fact that the driver of the socio-economic upliftment of the country is the activation of business processes in the industrial sector of the regional economy. It was noted that the existing industrial policy needs improvement and the formation of such directions of development that will consider new challenges of a global and national nature, including the spread of digitalization in all spheres of social life. In this connection, the need to assess the current level of regional concentration of industry has been updated. The peculiarities of the development of the industrial sector in the economy of the regions of Ukraine are determined based on the calculation of the localization (concentration) coefficient as the ratio of the concentration of a specific type of industrial activity (industry) in a separate region to its national value. Groups of regions are distinguished depending on the obtained values ​​of the localization (concentration) coefficient: regions with a high, medium, and low concentration of industrial activity (industry). It was determined that during 2014-2020, the dynamics of changes in the share of gross added value of the industry in the structure of gross added value of the economy of Ukraine had a general downward trend due to a decrease in the share of gross added value of all types of industrial activity. The role of the industrial sector in the production of gross added value of regional economies has been reduced. It was established that in the analyzed period, the number of regions with a high concentration of the industrial sector in the economy decreased by 1.3 times. More than half of all regions of the country had a level of industrial sector concentration lower than the national average. It was recorded that Dnipropetrovsk, Donetsk, Zaporizhzhya, Ivano-Frankivsk and Kharkiv regions maintained a consistently high level of concentration of the industrial sector. It was concluded that the current level of development of the country is characterized by regional disproportions in the production of gross added value of types of industrial activity and industry. It was noted that improving the business process management mechanism in the industrial sector of the regional economy requires a mutually beneficial partnership between representatives of business, authorities, scientific and technical institutions, and the public.
Keywords: industrial sector, gross added value, localization coefficient, concentration of production, region